La semblanza de Constantino en la obra de Libano - Moreno Resano, Esteban (Gerión. Revista de Historia Antigua, 2006)
The orator Libanius commented in eight of his speeches (I, XII, XVIII, XIX, XX, XXX, XLIX and LIX) several aspects of the emperor Constantine´s personality and government. In the last fifty years, some studies have been dedicated to the historical analysis of the passages concerning the question. The main trouble on that subject is how to establish a joint interpretation of the passages, since some ones expressed a positive discernment about the emperor, yet in another cases, it is so negative. Recently, H. U. Wiemer resolved that the variations in the Libanius´ judgement about Constantine answered to an evolution in his opinion on the emperor. Even though, this study defends that such variations respond to the rethorical use of the biographic notices on Constantine as exempla.